[PP.07.19] CORRELATION STUDY BETWEEN GENETIC POLYMORPHISMS HYPERTENSION-ASSOCIATED AND GENOMIC ANCESTRY IN A SAMPLE OF ADMIXED HYPERTENSIVE INDIVIDUALS FROM RIO DE JANEIRO, BRAZIL. (September 2016) - Machado, Y.; Freitas, R.; Pozzan, R.; Faria, R.; Campana, E.; Magalhaes, M.; Brandao, A.; Silva, D.
Abstract : Objective: To investigate if the genetic structure of admixed subjects is correlated with a distribution of genetic polymorphisms hypertension-associated. Design and method: DNA samples obtained from 178 normotensive and 113 hypertensive individuals were genotyped for four polymorphisms hypertension-associated [Insertion/Deletion angiotensin-I converting enzyme (I/D ACE), Ser49Gly and Arg389Gly of beta1-adrenergic receptor and M235T of angiotensinogen] and 46 ancestry informative markers (AIMs-Indels); their genotypic and allelic frequencies and ancestry estimates were calculated and compared between the clinical groups. Results: Normotensive and hypertensive individuals have a similar genetic diversity for both genetic polymorphisms (44.59% and 44.95% and for AIMs (38.85% and 40.37%), whereas the European alleles were over-represented in both clinical groups (48–60%), followed by the African (25–39%) and, finally, Amerindians (12–14%). The presence of hypertension was detected in 68.8% of Afro-descendants, 47.5% of mixed-race and only 33.3% of euro-descendants (χ 2  = 8, 420; p = 0.015). There was no difference in the distribution of the genotypes of Arg389Gly and Ser49Gly between normotensives and hypertensives (p = 0.702 and p = 0.574, respectively), but there was difference in M235T where the MM genotype was more prevalent in normotensives while the TT genotype was more prevalent in hypertensives (30.8%; 41.9%; χ 2  = 18, 375; p = 0.000). A higher prevalence of the II genotype was observed in hypertensive when compared to normotensive (21.9% versus 8.3%; χ 2  = 9, 944; p = 0.007). Ultimately, the ancestry genomic of individuals showed that only the TT genotype of the M235T polymorphism presented different distribution between groups, which was the most frequent genotype in afro-descendants (56.3%; χ 2  = 12, 993; p = 0.011). Conclusions: The findings suggest that African ancestry exhibited influence on the prevalence of hypertension in the sample and that despite the polymorphisms ACE and M235T have presented different distributions between the groups, the ancestry genomy of the individuals revealed that only one of the four markers evaluated showed association with an ethnic group without any influence on the distribution of the other one.